Seroepidemiological Study of Outdoor Recreationists' Exposure to Spotted Fever Group Rickettsia in Western Australia - Abdad, Mohammad Y. (The American Society of Tropical Medicine and Hygiene, 2014)
Bushland activity has previously been linked to rickettsial exposure in eastern and central regions of Australia, whereas little is known about the risks in Western Australia. The isolation of Rickettsia gravesii sp. nov. from Amblyomma triguttatum ticks and anecdotal reports of low-grade illness among bush recreationists raised the possibility of rickettsial transmission in the State. This study investigated rickettsial seroprevalence and potential risk of exposure to the spotted fever group rickettsiae in rogainers. Our results showed that rogainers active in the bush had a significantly higher risk of seropositivity (immunofluorescence total antibody titer ≥ 128) for the spotted fever group Rickettsia (odds ratio [OR] = 14.02, 95% confidence interval [CI] = 1.38–142.07) compared with a reference population, the overall seroprevalence in the rogainer group being 23.1%.